Chronic Lung and Gastrointestinal Diseases: Take a Broader Perspective - Syifa Mustika; Tiar Oktavian Effendi (Faculty of Medicine Universitas Airlangga, 2022)
Chronic lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD), are often found with gastrointestinal symptoms or even gastrointestinal diseases as one of its comorbid. Vice versa, many cases of gastrointestinal diseases such as gastroesophageal reflux disease (GERD) have developed respiratory dysfunction later. The connection between these two systems has become interesting lately and has led to several studies to prove the association. Several theories have emerged to explain this association. This includes changes in microbiota, the mucosa-related immune system of both systems, side effects of the therapeutic given, and pathomechanism related to gastrointestinal diseases such as GERD. Many studies try to prove the connection between the microbiota in the respiratory and gastrointestinal system, and changing the abundance in one of the systems can affect another. Both of the systems also have a similar mucosal membrane in their lining. Those membranes have an immune defence called Mucosal-Associated Lymphoid Tissue (MALT). Lymphatic and circulatory systems facilitate the migration between two mucosal, and these interconnections influence each other. Although the side effect of the therapeutic agent in respiratory diseases (such as inhaled corticosteroid, beta-2 agonist, or anti-cholinergic) is thought to be one of the causative mechanisms, discontinuation of therapy is the second option. Probiotic supplementation to improve microbiota is still not a strong recommendation for management.